Grb2 Is Important for T Cell Development, Th Cell Differentiation, and Induction of Experimental Autoimmune Encephalomyelitis - Radtke, Daniel; Lacher, Sonja M.; Szumilas, Nadine; Sandrock, Lena; Ackermann, Jochen; Nitschke, Lars; Zinser, Elisabeth (Journal of Immunology, 2016)
The small adaptor protein growth factor receptor-bound protein 2 (Grb2) modulates and integrates signals from receptors on cellular surfaces in inner signaling pathways. In murine T cells, Grb2 is crucial for amplification of TCR signaling. T cell-specific Grb2(fl/fl) Lckcre(tg) Grb2-deficient mice show reduced T cell numbers due to impaired negative and positive selection. In this study, we found that T cell numbers in Grb2(fl/fl) CD4cre(tg) mice were normal in the thymus and were only slightly affected in the periphery. Ex vivo analysis of CD4(+) Th cell populations revealed an increased amount of Th1 cells within the CD4(+) population of Grb2(fl/fl) CD4cre(tg) mice. Additionally, Grb2-deficient T cells showed a greater potential to differentiate into Th17 cells in vitro. To test whether these changes in Th cell differentiation potential rendered Grb2(fl/fl) CD4cre(tg) mice more prone to inflammatory diseases, we used the murine Th1 cell-and Th17 cell-driven model of experimental autoimmune encephalomyelitis (EAE). In contrast to our expectations, Grb2(fl/fl) CD4cre(tg) mice developed a milder form of EAE. The impaired EAE disease can be explained by the reduced proliferation rate of Grb2-deficient CD4(+) T cells upon stimulation with IL-2 or upon activation by allogeneic dendritic cells, because the activation of T cells by dendritic cells and the subsequent T cell proliferation are known to be crucial factors for the induction of EAE. In summary, Grb2-deficient T cells show defects in T cell development, increased Th1 and Th17 cell differentiation capacities, and impaired proliferation after activation by dendritic cells, which likely reduce the clinical symptoms of EAE.